2021
DOI: 10.3389/fmicb.2021.717045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action, Resistance, Synergism, and Clinical Implications of Delamanid Against Multidrug-Resistant Mycobacterium tuberculosis

Abstract: Multidrug-resistant (MDR) isolates of Mycobacterium tuberculosis (MTB) remain a primary global threat to the end of tuberculosis (TB) era. Delamanid (DLM) is a nitro-dihydro-imidazooxazole derivative utilized to treat MDR-TB. DLM has distinct mechanism of action, inhibiting methoxy- and keto-mycolic acid (MA) synthesis through the F420 coenzyme mycobacteria system and generating nitrous oxide. While DLM resistance among MTB strains is uncommon, there are increasing reports in Asia and Europe, and such resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 95 publications
(137 reference statements)
0
20
0
1
Order By: Relevance
“…Andreas H. Diacon (12) also found that the CFU of smear-positive pulmonary tuberculosis patients decreased rapidly after treatment with Dlm for 2 days. It was suggested that Dlm may accumulate in the cell and has potential activity against the intra-and extracellular bacilli (13). Thirdly, the bactericidal activity of Dlm was concentrationdependent.…”
Section: Discussionmentioning
confidence: 99%
“…Andreas H. Diacon (12) also found that the CFU of smear-positive pulmonary tuberculosis patients decreased rapidly after treatment with Dlm for 2 days. It was suggested that Dlm may accumulate in the cell and has potential activity against the intra-and extracellular bacilli (13). Thirdly, the bactericidal activity of Dlm was concentrationdependent.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits bacterial respiration. [27,28] F I G U R E 2 Delamanid and TBA-354 are the modified versions of pretomanid…”
Section: Pretomanid (Pa-824)mentioning
confidence: 99%
“…The obtained compounds were evaluated for their anti-TB activity out of which three compounds (25-27) (Figure 13) were chosen as the hit compounds, each with an MIC value of 1 μg/ml in the first screening and MIC of 0.625 μg/ml in the second screening against mycobacterial H 37 Rv strain. [125] There was a significant increase in activity of the hit moieties due to the substitution of the substituent groups (Me [25], 4-trifluoromethylphenyl [26], and dimethylamino [27]). Docking of receptor enoyl-ACP reductase was used to identify the mode of action of the active compounds 25-27.…”
Section: Fluoroquinolone Is a Promising Subunit In Treating Tbmentioning
confidence: 99%
“…Delamanid (12) is recognized as an inhibitor of mycolic acid synthesis [19] and is thought to undergo the same activation process and exhibit the same mechanism of action as pretomanid (6).…”
Section: Tuberculosismentioning
confidence: 99%
“…Fungal endophyte PSU-N24 was isolated from the branch of Garcinia nigrolineata collected in Thailand, and was fermented to produce 9α-hydroxyhalorosellinia A (18), which was found to have an MIC of 13.3 µg/mL after testing against M. tuberculosis H37Ra [26]. Desoxybostrycin (19) and 9β-hydroxydihydrodesoxybostrycin (20) produced by the same fungus were found to be less active against M. tuberculosis H37Ra, having an MIC of 50 and 25 µg/mL, respectively [26]. Diaporthe sp.…”
Section: Compounds From Endophytic Fungi and Plant-pathogenic Fungimentioning
confidence: 99%